Predictors of hypertension in an urban HIV-infected population at the University of Calabar Teaching Hospital, Calabar, Nigeria - Okpa HO (Dove Medical Press, 2017)
Henry Ohem Okpa,1 Elvis Mbu Bisong,2 Ofem Egbe Enang,1 Emmanuel Monjok,2,3 Ekere James Essien3 1Department of Internal Medicine, 2Department of Family Medicine, University of Calabar and University of Calabar Teaching Hospital, Calabar, Nigeria; 3Institute of Community Health, University of Houston, Texas Medical Center, Houston, TX, USA Background: The introduction of highly active antiretroviral therapy (HAART) has remarkably improved the prognosis of human immunodeficiency virus (HIV)-infected patients, at the expense of the development of long-term complications such as cardiovascular and renal diseases. Hypertension (HTN) is a major risk factor for cardiovascular diseases and its associated mortality. In this study, we aimed to determine the prevalence of HTN and to identify possible predictors among HIV-infected patients attending the HIV Special Treatment Clinic at the University of Calabar Teaching Hospital, Calabar.Materials and methods: A cross-sectional study was carried out over a 5-month period from February to July 2016. A total of 112 HIV-infected persons were consecutively recruited and their blood pressures were measured in two consecutive clinic visits. They were compared with the HIV-negative control group (n=309). Data collected were analyzed with SPSS 18, and statistical significance was set at P<0.05.Results: There was a female preponderance in both the HIV-infected individuals and HIV-negative control group (57.5% vs. 57.4%). The mean ages were 39.3 and 33.9 years in HIV-infected and HIV-negative subjects, respectively. The risk factors that were associated with HTN in both groups were older age (>40 years), increased weight and body mass index (BMI), and presence of obesity. Male sex and duration of exposure to HAART and CD4 count levels >200 cells/mm3 were associated with HTN in HIV-infected patients, whereas the absence of family history of HTN was significantly associated with HTN in both groups. However, in a multivariate logistic regression, the predictors of HTN in both groups are absence of family history of HTN and older age in HIV-infected patients and HIV-negative subjects, respectively.Conclusion: Traditional risk factors such as older age, increased BMI, and obesity were linked to HTN in both HIV-infected and HIV-negative subjects, but higher CD4 count level and cumulative HAART exposure were associated with HTN in HIV-positive individuals. In a multivariate logistic regression, the predictors of HTN in both groups are absence of family history of HTN and older age in HIV-infected patients and HIV-negative subjects, respectively. Keywords: hypertension, urban, HIV, population, Calabar, Nigeria